2018
DOI: 10.3991/ijep.v8i4.8126
|View full text |Cite
|
Sign up to set email alerts
|

Game-Based Learning while Research Activities of Engineering Students

Abstract: This work describes the experience of Tomsk Polytechnic University in involving students in scientific research. The involvement is to be achieved by including scientific research elements into laboratory class programs, game-based learning, conducting laboratory classes in real-life scientific research facilities, including "Scientific research work for students" into Bachelor's curriculum (starting the second grade) and other actions. The experience described should be considered a success, as over the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Typically, the traditional method involves translating lecture content into calculations in paper-based design exercise, which involved doing truth table calculations or Karnaugh mapping for circuitry connection, for example. To support this teaching method, encouraging "learning while doing" approach in system design projects can help students to connect their learned concept from lectures to practical development [6][7][8]. In this case, educational tools can be implemented to improve student understanding.…”
Section: Key Outcome Of Learningmentioning
confidence: 99%
“…Typically, the traditional method involves translating lecture content into calculations in paper-based design exercise, which involved doing truth table calculations or Karnaugh mapping for circuitry connection, for example. To support this teaching method, encouraging "learning while doing" approach in system design projects can help students to connect their learned concept from lectures to practical development [6][7][8]. In this case, educational tools can be implemented to improve student understanding.…”
Section: Key Outcome Of Learningmentioning
confidence: 99%
“…Starting from the 80s, different attempts were made in order to enhance creativity and innovation [16] [20], that is, the identification of best practices such as:…”
Section: Contextmentioning
confidence: 99%
“…Teamwork is often associated with game-based learning, but also with project-based learning [21] [22]. Vodernichova [23], who applied play in higher education, concluded that simulation play in teams deepens knowledge and skills, increases creativity and confidence, as well as motivation and interest.…”
Section: Introductionmentioning
confidence: 99%